Pemikiran Melayu : kolot atau progresif - AB Sulaiman, 1943- (Malaysia : Abu Bakar Bin Hj Sulaiman, 2023)
Thought and thinking of Malay philosophy in Malaysia.
Includes index.
Keywords: Malays (Asian people) -- Malaysia -- Social life and customs; Malays (Asian people) -- Ethnic identity -- Malaysia; Malays (Asian people) -- Malaysia -- Social conditions; Malays -- Attitudes